Training for Emis 4.0 Operators at TPQ Nurul Huda Ngariboyo Hamlet Sindupaten Village Kertek District - Munafiah; Ibadiyatul Istiqomah; Amirul Rahmat Alfaisal; Kurniawati Mutmainah; Ahmad Khoiri (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2025)
EMIS 4.0 represents an innovative framework that integrates cutting-edge information technology with educational management systems. Within the EMIS 4.0 framework, data and information pertaining to educational services, including Islamic religious universities, madrasahs, Islamic boarding schools, as well as student, teacher, and educational facility data, are systematically collected, managed, and analyzed using advanced information and communication technology. This study employs qualitative research methods, encompassing observation, interviews, and documentation. The program is structured in two phases, involving EMIS operators, the Head of the TPQ, and the educators at Nurul Huda TPQ. The initial phase involves program socialization at the residence of the TPQ Head and the Nurul Huda TPQ operators, aiming to identify challenges associated with data entry into EMIS. The subsequent phase comprises joint training sessions for operators, teachers, and the Head of Nurul Huda TPQ, with the objective of ensuring that EMIS operators can efficiently input data into the EMIS application. Challenges identified during the EMIS socialization activities included insufficient media resources, slow internet connectivity, operators' unfamiliarity with laptop usage, and the lack of standardized technical guidelines at the TPQ level. The training effectively enhanced operators' comprehension of the significance of digital data collection, illustrating that practical, hands-on experience is more efficacious than theoretical instruction or lectures alone..